Cytotoxic and antibacterial properties of piper betle combined with selected root canal sealers - Chen, Wei Qi; Huwaina Abd Ghani; Suharni Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2023)
Exploration in endodontic material had been made to maximise the elimination of microorganisms in root canal system to improve the treatment success rate. Inappropriate use of antibiotics can cause antibiotic resistance hence alternative is needed. Piper betle (PB), a medicinal herb to be used for its effective antibacterial properties against Enterococcus faecalis. Therefore, this study aims to investigate the cytotoxicity and antibacterial effects of ethanolic extract of PB in combination with AH Plus (AH) and BioRoot RCS (BR) and sealers alone. Four tested materials were used: AH Plus (AH); PB and AH plus (PBAH); BioRoot RCS (BR); and PB and BioRoot RCS (PBBR). At 24, 48, and 72 h, MTT assay on HPdLF was performed to measure the cytotoxicity. Antibacterial effect was evaluated with modified direct contact test (MDCT) against E. faecalis at fresh, day1-set and day-7-set state of tested materials. Data were analysed with SPSS version 25 with Tukey’s post-test at the level of significance of p = 0.05. PBAH showed significant lower cytotoxicity than AH (p = 0.028) at 48 h, with a higher percentage of cell viability compared AH (26.35%). PB reduce antibacterial effect of BR at all times at significant level (p = 0.000, 0.014, 0.032). Conclusion, PBAH has significant reduced cytotoxicity as compared to AH on HPdLF at 48 h. PBBR was cytotoxic to HPdLF at 24 and 48 h. Both AH and PBAH exhibited antibacterial property against E. faecalis, followed by BR and PBBR. In conclusion, PBAH is a potential enhanced root canal sealer and may be further studied to fully elicit its profound properties.